Growth, Instability, and Decomposition of Coconut Production in Gujarat: A Comprehensive Analysis of Trends and Dynamics - Kumar, Prabhat; Hanumanthe Gowda, B.; Yeswanth, Raghuramreddy (Journal of Plantation Crops, 2026)
Coconut (Cocos nucifera), often referred to as the “Kalpavruksha” is an economically vital crop. India, particularly its southern states, is a major producer of coconut, contributing significantly to GDP and supports around 12 million livelihoods (Murthy, B. N. S.2019)Gujarat, a non-traditional coconut-growing state, has witnessed a rise in coconut cultivation, especially in coastal districts like Kutch, Junagadh, Porbandhar, and Navasari. This study analyzed the growth, instability, and decomposition of coconut cultivation in Gujarat over the period 2000-2020, using secondary data.The statistical tools employed such as, Compound Annual Growth Rate (CAGR) was used to evaluate growth trends in area, production, and yield. Instability was assessed using Coefficient of Variation (CV) and Cuddy-Della Valle Index (CDVI), while decomposition analysis quantified the contributions of area, yield, and their interaction to production changes.The results reveal significant variability in growth in area and production across most districts, with Gujarat’s coconut area with a CAGR of 4.10 percent (2000-2020) and production 5.80percent.However, yield growth showed a decline of -0.87percentin Period II (2010-2020). Instability analysis revealed varying degrees of volatility, with Surat and Valsad showing the highest instability in area and production (CV of 30.05% and 46.68%, respectively), while Kutch displayed relatively stable growth. Decomposition analysis revealed that area expansion contributed significantly to production increases (41.54% in Period I, 127.96% in Period II), while yield effects were less consistent (-20.51% in Period II). This emphasizes the need for targeted interventions to enhance yield through better farming practices and climate-resilient varieties, alongside continued support for area expansion.